The devil's flute murders - Yokomizo, Seishi 1902-1981 (Pushkin Vertigo, 2023)
In 1947, Kindaichi is consulted by 20-something Mineko Tsubaki. Her father, Hidesuke, a flautist and composer, disappeared the previous spring, and his corpse was found six weeks later. The official verdict was that Hidesuke poisoned himself, but Mineko and her mother, who believe the corpse was misidentified, suspect he may still be alive. Kindaichi agrees to attend a divination session intended to summon the musician's spirit and confirm his demise, during which another member of the Tsubaki household is murdered. Now saddled with two cases, Kindaichi must suss out Tsubaki family secrets to prevent even more carnage